G528(P) A daily regional conference call: maximising efficiency of repatriation. the impact on neonatal units in the west of scotland. (27th April 2015) - Mitchell, J; Jackson, L; Elliot, J; Tait, F
Abstract : Context: This project has been carried out between the regional neonatal units, the Neonatal Managed Clinical Network (NMCN) and the Neonatal Transport team (NTS). It has involved multidisciplinary team work between all the health boards in the region with input from key medical, nursing and network staff. Problem: It became apparent to the NMCN that neonatal cot capacity in the region was frequently highly occupied and under pressure. We wanted to have a proactive method of identifying cot capacity issues early and maximise our repatriation processes whilst identifying any delays. As a trainee representative at the NMCN meetings, I suggested setting up a regional teleconference call to address these issues. A multidisciplinary team were tasked with setting up this call. Assessment of problem and analysis of its causes: The working group contacted key staff within the region's neonatal community to canvass opinion with regards to regional cot capacity issues. Discussions confirmed that issues with limited availability of cots often became apparent late in the day and left clinicians spending significant amounts of time locating cots. Units and NTS were not always aware what was happening elsewhere until multiple phone calls and time had been spent trying to find out such information. Consent was gained to set up a daily teleconference call between the units and NTS to obtain information about the regional cot capacity. Intervention: The call takes place each day at 12.30pm, chaired by the Transport Consultant. Each unit is represented by the Duty Consultant and/or Nurse in Charge. Information is collected upon unit status, staffing issues, cot availability, expected admissions and babies awaiting repatriation or transfer for specialist investigation. The call takes less than 15 min. The information is recorded by NTS and electronically shared with Network administration where it is regularly analysed. Study design: A PDSA cycle was undertaken to set-up, test, implement and analyse effectiveness of the intervention. Strategy for change: Mock calls were undertaken by the working group to trial the call, test the process of change and refine the data to be collected. Following small adjustments the call went live. A start date, time and telephone number was communicated with senior staff within the region. Data was collated. Measurement of improvement: Data was collated as above then analysed and shared with unit managers using real time figures and run charts. Analysis revealed that there were no delays in transport due NTS but that delays in repatriation due to receiving unit cot capacity issues are not uncommon. Effects of changes: When units are busy, other units in the region have worked together to relieve capacity issues when able. Units and NTS are aware earlier in the day what the cot issues are. Units are including the regional activity information in their handovers. The call allows efficient planning of workload and implementation of solutions more effectively. The teleconference call has now been extended to include large units elsewhere in the country. Lessons learnt: Through feedback and analysis, we have further refined the data collected, maximising call effectiveness. Data collection has demonstrated significant issues with cot capacity which will be used to campaign for funding for more cots and staff. Message for others: The conference call was rapid to implement and embed into clinical practice. This is because it is quick and addresses issues close to the priorities of all users. Transfers can be undertaken more efficiently, ultimately saving clinician time.